Scholē as a Way of Learning to Be Human in the Age of the Internet - Dancák, Pavol (Philosophy and Canon Law, 2023)
The article offers a brief philosophical reflection on scholē and human being in the context of the Internet. The first part of the article shortly explains the urgency of the problems that arise from the extensive use of the Internet, such as addiction to digital devices, being constantly connected to the Internet and receiving unreliable information. The second part of the article offers a reflection of scholē (leisure) as a space for transcendence which is a very important attribute of the human being and which is the foundation of our culture. Scholē is an organic component of culture and education, and leisure presents not the cessation of work, but a work of a rather different kind, the work restored to its human meaning, as a celebration and a festival. The article concludes that scholē provides us with precise and true information about what the human person essentially needs.